Should I Stay or Should I Go? Mycenaeans, Migration, and Mobility in the Late Bronze Age and Early Iron Age Eastern Mediterranean - Middleton, Guy D. (Journal of Greek Archaeology, 2018)
A recent paper argues that climate change at the end of the Late Bronze Age caused mass migrations, ‘vast movements of population’, out of the Balkans into Greece and Anatolia, with migrants destroying cities and states as they went – causing the collapse of Late Bronze Age societies such as the Mycenaeans. These migrants then became the Sea Peoples, who gathered more followers from the Aegean and set off for the eastern Mediterranean, destroying as they went, until they were finally defeated by Ramesses III in Egypt. The hypothesis, as with other similar arguments in the past, links together the history of the eastern Mediterranean, from Greece and Anatolia to Cyprus and the Levant and Egypt in one ‘global’ narrative.